Risk factors for late onset gram-negative infections: a case–control study. Issue 1 (10th June 2010) - Samanta, Srabani; Farrer, Kate; Breathnach, Aodhan; Heath, Paul T
Abstract : Objectives: To determine the incidence, mortality and risk factors for neonatal late onset gram-negative sepsis and meningitis (LOGNS). Design: Retrospective case–control study. Setting: Tertiary neonatal unit in London. Patients: Consecutive inborn infants with late onset (>48 h of life) invasive gram-negative infections diagnosed between 1999 and 2005. Controls were healthy infants matched for gestation and time of admission to the neonatal unit. Main outcome measures: Clinical and risk factor data. Results: 73 cases of LOGNS were identified of which 48 were inborn and included in the study (incidence 1.85/1000 live births). Enterobacter spp. (28%), Escherichia coli (27%) and Klebsiella spp. (21%) were the most common pathogens. The majority of infants were of very low birthweight (VLBW; 79%), and cases and controls were well matched (median gestation 26 weeks). Overall case death was 27% in cases versus 13.5% in controls (p=0.08). There was no significant difference between cases and controls regarding maternal risk factors. Mechanical ventilation, total parenteral nutrition (TPN) and its duration, presence of a central venous line and its duration, use of specific antibiotics and the occurrence of necrotising enterocolitis at or before the first positive culture were all significantly associated with case status in univariate analysis. In multivariate logistic regression analysis, only duration of TPN at or before first positive blood culture remained independently associated with LOGNS (p<0.001). Conclusions: LOGNS occurs predominantly in VLBW infants. When the influence of gestational age is accounted for, the only independent risk factor found for late onset gram-negative neonatal infections is the duration of TPN.